(untitled) (GESTIÓN Y TENDENCIAS, 2019)
This column argues for incorporating the human rights perspective into the conduct of business activity in Chile and, in particular, into the field of labor relations. After examining how this perspective has been defined by international bodies, the author underlines a number of outstanding challenges for companies and for the Chilean State.